Negative urgency, PTSD symptoms, and alcohol risk in college students - Hagar Hallihan; Hanaan Bing-Canar; Katherine Paltell; Erin C. Berenz (Addictive Behaviors Reports, 2023)
Introduction: Theoretical models of trauma and alcohol use suggest that trauma-exposed individuals with higher levels of PTSD symptoms are at increased risk of problematic and coping-oriented alcohol use to alleviate unwanted internal states. The goal of the current study was to evaluate whether these associations are enhanced among young adults who report engaging in impulsive behavior in the context of negative affect (i.e., high negative urgency). It was hypothesized that (a) higher negative urgency would be associated with problematic alcohol use; and that (b) negative urgency would moderate the association between PTSD symptoms and problematic alcohol use. Methods: This study used a cross-sectional, secondary data analysis design run on 213 participants: college students, ages 18–25, who endorsed both having an interpersonal traumatic event and current weekly alcohol use. Participants completed a series of assessments and self-report questionnaires. Results: Results of hierarchical linear regression models indicated that greater negative urgency was significantly associated with greater negative alcohol-related consequences and greater coping motives for alcohol, but not past 30-day binge frequency or past 30-day alcohol quantity. Negative urgency did not moderate associations between PTSD symptoms and alcohol outcomes. Conclusions: PTSD symptoms and negative urgency are uniquely associated with indices of alcohol risk in college students with a history of trauma exposure. However, individuals high in negative urgency are not necessarily consuming more alcohol, nor does negative urgency increase the association between PTSD symptoms and drinking outcomes in this population.